The Influence of Drip Irrigation with Mulch Cover on the Growth, Yield, and Water Use Efficiency of Black Tomato (Solanum lycopersicum l.) in Pots - , Nabanita Sarkar, Rupam Roy, Rudranil Dey, Progya Paromita Mondal, Moutushi Paul, Aditi Biswas, Disha Ghosh (Archives of Current Research International, 2025)
The field experiment was conducted at the Instructional Farm of Department of Agricultural Engineering, JISCE, Nadia, West Bengal in sandy loam soil to investigate the influence of drip irrigation with two mulches cover (polyethylene sheet and paddy straw) on growth, yield and water use efficiency of black tomato (Solanum Lycopersicum L.) in pots and conventional farming methods at different treatments. In the study, four irrigation treatments were applied with four replications. The different irrigation treatments were follows: (i) T1- Conventional irrigation with 5 cm of water in each irrigation after disappearance of water, (ii) T2 - 0.8 Epan under drip irrigation @ 4 l/h at 1 day interval with plastic mulching, (iii) T3 - 0.6 Epan under drip irrigation @4 l/h at 1 day interval in pots, (iv) T4 - 0.4 Epan under drip irrigation @ 4 l/h at 1 day interval in pots with straw mulching. Results showed that the water requirements under drip irrigation for all treatments were lower compared to conventional (flooding) irrigation. The amount of irrigation water required under drip irrigation with straw mulch cover in pots at T4 -0.4 Epan treatments is the lowest, i.e, 150 mm, and the highest value was 562 mm at T1 treatments i.e, in the conventional irrigation system. The amount of irrigation water required under T2 and T3 was 300 mm and 225 mm, respectively, over the 75 days. It was found that the average yield at T1, T2, T3, and T4 treatments was 80 t/ha, 112 t/ha, 96 t/ha, and 120 t/ha, respectively. It was observed that the water use efficiency was found to be the highest at the treatment of T4 0.4 Epan of drip irrigation with straw mulching in pots was 120 t/ha-cm. The study demonstrates that drip irrigation in combination with different mulch significantly increased the plant height, dry matter production, number of fruits per plant, fruit weight and finally raised the black tomato yield to 120 t/ha with 73 % water saving compare to conventional method of irrigation (flooding) practiced by most of the farmers.